2014
DOI: 10.4103/0976-500x.124419
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxicity of cefepime: A new cephalosporin antibiotic in rats

Abstract: Objectives:To investigate the nephrotoxic effect and biochemical alterations induced by cefepime in rats.Materials and Methods:Cefepime was administered intramuscularly at doses of 45, 90 and 180 mg/kg b.wt. once daily for 5 consecutive days. The serum and urine samples were used for quantitative determination of urea, creatinine, glucose, total protein, calcium, sodium and potassium. The histopathological examination of kidney tissues was performed 1, 4 and 8 days after the last dose of cefepime administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 16 publications
5
32
0
1
Order By: Relevance
“…The current findings suggested that proximal convoluted tubules were the frequently affected renal tubular cells, that attributed to cellular metabolic pathways are greatly vulnerable to nephrotoxic agents as DS (Elsayed et al, 2014). And this is supported by others observation (Sabry et al).…”
Section: Discussionsupporting
confidence: 87%
“…The current findings suggested that proximal convoluted tubules were the frequently affected renal tubular cells, that attributed to cellular metabolic pathways are greatly vulnerable to nephrotoxic agents as DS (Elsayed et al, 2014). And this is supported by others observation (Sabry et al).…”
Section: Discussionsupporting
confidence: 87%
“…Semisynthetic penicillins, including piperacillin‐tazobactam, likely cause AKI through an acute interstitial nephritis (AIN)‐mediated mechanism that was described in numerous case reports . A single case report and pharmacokinetic studies in rats have demonstrated that cefepime may cause AKI due to an AIN‐mediated mechanism as well; however, further evaluation into this potential mechanism is needed . The exact mechanism behind AKI due to β‐lactams and vancomycin is unknown; however, an additive effect of AIN and direct cellular necrosis may be responsible …”
Section: Discussionmentioning
confidence: 99%
“…9-14, 53, 54 A single case report and pharmacokinetic studies in rats have demonstrated that cefepime may cause AKI due to an AIN-mediated mechanism as well; however, further evaluation into this potential mechanism is needed. 55,56 The exact mechanism behind AKI due to b-lactams and vancomycin is unknown; however, an additive effect of AIN and direct cellular necrosis may be responsible. 4,10,11,13,14 To our knowledge, this is the first evaluation of an entirely critical care population for the effects of vancomycin and concomitant piperacillin-tazobactam or cefepime on AKI development.…”
Section: Risk Of Aki With Vancomycin and B-lactams In Critically Ill mentioning
confidence: 99%
“…Those substances appear in the urine if plasma level exceeds or when renal tubules defects, possibly resulting in nephrotoxicity. 20 Thus, urine sodium and potassium levels can predict its correlation as demonstrated in the present study. Measurements for 24-h urinary sodium in group V presented low concentration of urinary sodium.…”
Section: Discussionmentioning
confidence: 71%